The role of seed phytic acid levels in promoting black rice growth, nutrient use efficiency, and yield under low-input conditions - Oo, Aung Zaw; Asai, Hidetoshi; Songyikhangsuthor, Khamdok; Vongphouthone, Banthasack; Takai, Toshiyuki; Marui, Junichiro; Saito, Hiroki; Vilayheuang, Koukham (Frontiers in Agronomy, 2026)
Black rice is cultivated in Southeast Asia’s upland and lowland area, where yields are often limited by low soil fertility, phosphorus (P) deficiency, and limited external inputs. Phytic acid (PA)—the principal storage form of P in rice seeds—represents more than 70% of the total seed P. Data on the effects of seed PA levels on the agronomic performance of black rice, especially under upland field conditions, are scarce. This study explored the effect of seed PA concentration on the early growth, nutrient uptake, and yield performance of black rice under both pot and upland field conditions. In pot experiments, we tested three levels of seed PA (low, moderate, and high) at different soil P applications (control, low P, and high P). A complementary field trial in Luang Prabang, Laos, evaluated the effects of seed PA and nitrogen (N) application (0 or 30 kg N ha-1) under rainfed conditions. Results demonstrated that high-PA seeds significantly improved early seedling vigor, shoot and root biomass, and nutrient uptake, particularly under conditions of low or no external P supply. At maturity, high-PA plants yielded 35% more grain than that yielded by low-PA plants in pots and exhibited a 47% yield advantage in upland fields. Low N input did not affect grain yield but notably reduced grain PA levels under upland conditions. Overall, the findings indicate that seed PA concentration is a key physiological trait that enhances the adaptation and productivity of black rice in nutrient-poor upland systems.